A Brief Note on the Relationship between Anxiety and Performance in Scuba Diving in Adolescents: A Field Study. Issue 3 (June 2015) - Steinberg, Fabian; Doppelmayr, Michael
This study explored the relationship between anxiety and scuba diving performance of young individuals ( N = 44; 16.9yr., SD = 1.2) participating in an introductory scuba diving activity. The question was whether the well-known negative correlation between anxiety and scuba diving performance found for experienced and middle-aged scuba divers will be observed in young participants in their first dive experience. Diving instructors rated standardized scuba diving skills that were correlated with individual state and trait anxiety. There was no relationship between anxiety and scuba diving performance, neither for state nor for trait anxiety. This non-significant correlation between anxiety and performance was in contrast to recent findings observed for experienced divers or those who participated at a scuba diving training program. Considering the differences in methodological design between this study and recent investigations, further research is needed to reveal possible relations between anxiety, scuba diving performance, and panic behavior in beginner-level youth or adults.